What did the notion of entropy introduce into philosophy? - Janusz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
In the article the emergence of notions: energy and entropy is studied. New physical discoveries were interesting for the domain of natural theology as well. The evolution of the notions in physics makes sometimes too simplistic expectations for philosophy of scientists. As an example Ostwald’s energetism is given, where even ethics had its energetic imperative. On the other hand Fourier’s type of philosophical elements in science is shown where fundamental role of mathematics is presupposed.